(untitled) (Research, Society and Development, 2022)
Objectives: To identify patients with suspected sarcopenia and to assess its association with nutritional status and clinical outcome. Patients and methods: Prospective study with cardiac patients admitted to the Coronary Unit. Subjective Global Assessment (SGA), nutritional assessment by body mass index (BMI), calf circumference (CC) measurement and screening for suspected sarcopenia by SARC-CalF were performed. Results: Forty patients (27H/13M;60.2±10 years) were studied, with an average length of stay (LS) of 13.4±7.6 days, and a 7.5% prevalence of deaths. Of the 37 patients screened by SARC-CalF, 09 (24.3%) were suspected of sarcopenia. By SGA, 29 (72.5%) patients were well nourished and 11 (27.5%) malnourished/nutritional risk. According to the BMI, 25 (62.5%) were overweight, 12 (30.0%) were eutrophic and 03(7.5%) lean. SGA was more sensitive to identify well-nourished (P=0.0003) and malnourished (P=0.0367) patients. Lower mean BMI (P=0.0049) and CC (P=0.0004) were observed in those suspected of sarcopenia. The group with suspected sarcopenia had more eutrophic patients (P=0.0106), and the group without suspected higher prevalence of overweight (P=0.0006). The death outcome was more present in those at nutritional risk/malnourished by SGA (P=0.0036). There was no difference between the groups regarding LS, presence of infection, readmission and death (P>0.05). Conclusion: There was an association of suspected sarcopenia with lower means of BMI and CC. Nutritional risk or malnutrition by SGA was associated with the occurrence of deaths, but there was no association of suspected sarcopenia with the clinical outcome.